Travel behaviour: a study of older Malaysians - Musa, G.; Sim, O.F. (Taylor & Francis (Routledge), 2010)
The worldwide demographic shift towards population ageing has made older adults an attractive market segment not only for developed countries but also for developing countries such as Malaysia. This study explores travel behaviour among older adults living in Malaysia. Using non-probability quota sampling, 1356 older adults responded to the personal interviews carried out in Peninsular Malaysia. The main travel motivations were ‘to spend time with friends or family’ and ‘relaxation’, and the most preferred destinations were big cities. The majority of the respondents preferred to travel in tour groups. Their decision to travel was largely influenced by cost and recommendations from their family. During their holiday, common problems faced by them were tiredness, health problems and worries over safety and security. There were significant differences with respect to their travel behaviour, among the different ethnic groups and religions. Based on the results, this paper provides some management implications to marketers and other tourism organisations.